2018
DOI: 10.14710/dijb.1.2.2018.55-70
|View full text |Cite
|
Sign up to set email alerts
|

The importance of spirituality dimensions in the development of entrepreneurship

Abstract: Human being as spiritual being needs to be nurtured spiritually so that they can be optimal in their work and their calling. Actualization of this calling can be made through entrepreneurship. The purpose of this study is to determine the importance of spiritual dimensions (vision, faith/hope, love altruistic, meaning/calling, membership) in the development of entrepreneurship (entrepreneurship intention, entrepreneurial networking, entrepreneurial capability, and entrepreneurial success). The analysis techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 31 publications
(44 reference statements)
1
7
0
3
Order By: Relevance
“…Another result of the present study showed that moral intelligence had a positive and direct effect on entrepreneurial attitude and this result with the results of Safari Jafarloo, Ghorbani, Zareiyan (2017) research on the effect of spiritual intelligence on entrepreneurial attitude and entrepreneurial intention and Sirine, Kurniawati (2018) was based on the effective role of ethics in entrepreneurship. In explaining this result, based on the opinion of Shahbaziyan Khonig, Hasani, Soleymani (2018), it can be said that the principles of moral intelligence include honesty (having moral values and acting accordingly and honestly) and responsibility.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Another result of the present study showed that moral intelligence had a positive and direct effect on entrepreneurial attitude and this result with the results of Safari Jafarloo, Ghorbani, Zareiyan (2017) research on the effect of spiritual intelligence on entrepreneurial attitude and entrepreneurial intention and Sirine, Kurniawati (2018) was based on the effective role of ethics in entrepreneurship. In explaining this result, based on the opinion of Shahbaziyan Khonig, Hasani, Soleymani (2018), it can be said that the principles of moral intelligence include honesty (having moral values and acting accordingly and honestly) and responsibility.…”
Section: Discussionsupporting
confidence: 89%
“…Cavus, Bicer (2016) concluded that there was a positive and significant relationship between innovation behaviors and ethics. In addition, the results of Safari Jafarloo, Ghorbani, Zareiyan (2018) showed that spiritual intelligence Sirine H, Kurniawati EP (2018), while researching, concluded that ethics had an effective role in improving entrepreneurship.…”
Section: Introductionmentioning
confidence: 99%
“… Antoncic and Prodan (2008) measured from a fourfold perspective: product services, renewal capabilities, innovation processes, and risk activities. Stone (2004) added autonomy and self-confidence on the basis of Miller, Sirine and Kurniawati (2018) divided ES into five dimensions: vision, faith/hope, altruistic love, meaning/calling, and membership.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Kemudian dilanjutkan praktek penerapan metode Six Sigma. Tahapan penerapan metode Six Sigma disampaikan pada gambar berikut (Moelyono & Trihandoyo, 2017) (Putri & Alfareza, 2019); (Fitria, 2020); (Sirine & Kurniawati, 2017); (T. A. T. Putra et al, 2017).…”
Section: Metodeunclassified
“…Pengembangan usaha konveksi dengan peningkatan kualitas produk, meliputi tahap perencanaan, pengorganisasian, pelaksanaan dan pengendalian. Dimana tahapan tersebut selaras dengan tahapan metode Six Sigma yakni Define, Measure, Analysis, Improve dan Control sebagai upaya pengembangan kualitas berkelanjutan (Sirine & Kurniawati, 2017), (Moelyono & Trihandoyo, 2017), (Putri & Alfareza, 2019), (Fitria, 2020). Apabila tahapan tersebut dilaksanakan dengan baik, akan berdampak baik pada usaha.…”
Section: Pembahasanunclassified